Effect of antibiofilm peptides on microbiological isolates obtained from raw cattle milk - Cruz Hernández, Claudia (2023)
The aim of the study was to evaluate the effect of four antibiofilm peptides (ACLL37-1, ACLL37-2, DLL37-1 and LL37-1) on microbiological isolates in raw cattle milk. An experimental descriptive pilot study was applied with milk samples from 14 milking cows. The microbiological isolation was made, the biofilm was extinguished by crystal violet, growth curves and the antibiofilm effect was evaluated with the peptides under study. From 56 milk samples, 41 microorganisms were isolated and 69.2% corresponded to negative coagulase-negative Staphylococcus (SCN). Likewise, 30 strains were identified as strong biofilm-forming adherents (73.2%) and 7 (17.1%) weakly adherents. In the growth curves with the peptides, an increase in the late lag phase was demonstrated and regarding the inhibitory effect of the peptides, it was found that they present a heterogeneous behavior compared to each isolate; however, the peptides with the highest percentage of inhibition were LL37-1, DLL37-1 and ACLL37-1. It is concluded that the peptides under study can be considered as a promising alternative in the inhibition of bacterial biofilm formation that can impact the udder health of specialized dairy cows.